THE RELATIONSHIP BETWEEN MINDFULNESS AND ACADEMIC RESILIENCE IN STUDENTS OF SYIAH KUALA UNIVERSITY, INDONESIA: CROSS-SECTIONAL STUDY - Sarah, Siti; Sari, Kartika; Iskandar; Amna, Zaujatul (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2024)
Background: Students can persist in pursuing education even though there are many demands which are a source of stress and even anxiety and depression. One of the factors of academic resilience comes from within the individual, namely mindfulness. Mindfulness is a state of being attentive and aware of the events at hand. Purpose: This study aims to determine the relationship between mindfulness and academic resilience in Syiah Kuala University students. Method: This study design used quantitative research with a sample of 330 students selected using the probability sampling method with disproportionate stratified random sampling technique. The Mindful Attention Awareness Scale (MAAS) and the Academic Resilience Scale (ARS-30) were used as research data collection instruments. Results: hypothesis testing using statistical analysis showed a significance value (p)=0.000 (p<0.05). This means that there was a positive relationship between mindfulness and academic resilience in Syiah Kuala University students. It means that the higher the student's mindfulness, the higher the academic resilience, and conversely. On the other hand, the lower the mindfulness, the lower the student's academic resilience ability. Conclusion: This study provides recommendations for future researchers to analyze other factors that influence academic resilience in the hope of producing more comprehensive data. Abstrak Latar Belakang: Mahasiswa mampu bertahan menempuh pendidikan meskipun banyak tuntutan yang menjadi sumber stress hingga kecemasan dan depresi. Salah satu faktor ketahanan akademik berasal dari dalam diri individu, yaitu mindfulness. Mindfulness adalah keadaan penuh perhatian dan sadar terhadap kejadian yang sedang dihadapi. Tujuan: penelitian ialah untuk mengetahui hubungan mindfulness dengan resiliensi akademik pada mahasiswa Universitas Syiah Kuala. Metode: Desain penelitian ini menggunakan penelitian kuantitatif dengan sampel sebanyak 330 mahasiswa yang dipilih menggunakan metode probability sampling dengan teknik disproportionate stratified random sampling. Mindful Attention Awareness Scale (MAAS) dan the Academic Resilience Scale (ARS-30) digunakan sebagai instrumen pengumpulan data penelitian. Hasil: uji hipotesis menggunakan analisis statistik menunjukkan nilai signifikansi (p)=0,000 (p<0,05). Artinya terdapat hubungan positif antara mindfulness dan resiliensi akademik pada mahasiswa Universitas Syiah Kuala, yang artinya semakin tinggi mindfulness pada mahasiswa maka semakin tinggi resiliensi akademik, dan sebaliknya semakin rendah mindfulness, maka semakin rendah kemampuan resiliensi akademik mahasiswa. Kesimpulan: Penelitian ini menyajikan rekomendasi bagi peneliti selanjutnya agar dapat menganalisis faktor lain yang mempengaruhi resiliensi akademik dengan harapan dapat menghasilkan data yang lebih komprehensif.